Airway and ventilation management strategies for hemorrhagic shock. To tube, or not to tube, that is the question!. Issue 6 (June 2018) - Hudson, Anthony J.; Strandenes, Geir; Bjerkvig, Christopher K.; Svanevik, Marius; Glassberg, Elon
Abstract : abstract: Many standard trauma management guidelines advocate the early use of endotracheal intubation (ETI) and positive pressure ventilation as key treatment interventions in hemorrhagic shock. The evidence for using these airway and ventilation strategies to manage a circulation problem is unclear. The potentially harmful effects of drug-assisted intubation and positive pressure ventilation include reduced cardiac output, apnea, hypoxia, hypocapnea (due to inadvertent hyperventilation), and unnecessarily prolonged on-scene times. Conversely, the beneficial effects of spontaneous negative pressure ventilation on cardiac output are well described. Few studies, however, have attempted to explore the potential advantages of a strategy of delayed intubation and ventilation (together with a policy of aggressive volume replacement) in shocked trauma patients. Given the lack of evidence, the decision making around how, when, and where to subject shocked trauma patients to intubation and positive pressure ventilation remains complex. If providers choose to delay intubation, they must have the appropriate skills to safely manage the airway and recognize the need for subsequent intervention. If they decide to perform intubation and positive pressure ventilation, they must understand the potential risks and how best to minimize them. We suggest that for patients with hemorrhagic shock who do not have a compromised airway and who are able to maintain adequate oxygen saturation (or mentation if monitoring is unreliable), a strategy of delayed intubation should be strongly encouraged. LEVEL OF EVIDENCE: Review article, level IV.